Recombinant human TIM-3 ectodomain expressed in bacteria and recovered from inclusion bodies as a stable and active molecule - Lima, G. C.; Chura-Chambi, R. M.; Morganti, L.; Silva, V. J.; Cabral-Piccin, M. P.; Rocha, V.; Medina, T. S.; Ramos, R. N.; Luz, D. (Frontiers in Bioengineering and Biotechnology, 2023)
Microbial system, such as Escherichia coli, as host recombinant expression is the most versatile and the cheapest system for protein production, however, several obstacles still remain, such as recovery of soluble and functional proteins from inclusion bodies, elimination of LPS contamination, incomplete synthesis, degradation by proteases, and the lack of post-translational modifications, which becomes even more complex when comes to membrane proteins, because they are difficult not only to produce but also to keep in solution in its active state. T-cell Immunoglobulin and Mucin domain 3 (TIM-3) is a type I transmembrane protein that is predominantly expressed on the surface of T lymphocytes, natural killer (NK) cells, dendritic cells, and macrophages, playing a role as a negative immune checkpoint receptor. TIM-3 is composed of a single ectodomain for interaction with immune system soluble and cellular components, a transmembrane domain, and a cytoplasmic tail, responsible for the binding of signaling and scaffolding molecules. TIM-3 pathway holds potential as a therapeutic target for immunotherapy against tumors, autoimmunity, chronic virus infections, and various malignancies, however, many aspects of the biology of this receptor are still incompletely understood, especially regarding its ligands. Here we overcome, for the first time, the challenge of production of active immune checkpoint protein recovered from bacterial cytoplasmic inclusion bodies, being able to obtain an active, and non-glycosylated TIM-3 ectodomains (TIM-3-ECD), which can be used as a tool to better understand the interactions and roles of this immune checkpoint. The TIM-3 refolding was obtained by the association of high pressure and alkaline pH. The purified TIM-3-ECD showed the correct secondary structure and was recognized from anti-TIM-3 structural-dependent antibodies likewise commercial TIM-3-ECD produced by mammal cells system. Furthermore, immunofluorescence showed the ability of TIM-3-ECD to bind to the surface of lung cancer A549 cells and to provide an additional boost for the expression of the lymphocyte activation marker CD69 in anti-CD3/CD28 activated human PBMC. Taken together these results validated a methodology able to obtain active checkpoint proteins from bacterial inclusion bodies, which will be helpful to further investigate the interactions of this and others not yet explored immune checkpoints.